2013
DOI: 10.1186/1475-2840-12-66
|View full text |Cite
|
Sign up to set email alerts
|

Early impairment of contractility reserve in patients with insulin resistance in comparison with healthy subjects

Abstract: BackgroundInsulin resistance (IR) is currently considered a crucial cardiovascular (CV) risk factor, which seems to play a dominant role in the evolution toward cardiac and vascular impairment. Early IR-induced cardiac dysfunction can be assessed by Doppler-derived myocardial systolic strain rate (SR) index, measured at baseline and after dobutamine stress echocardiography (DSE).MethodsThirty IR patients (HOMA-IR = 7 ± 5.2, age 52.6 ± 2.1 years), and 20 healthy, age and sex matched controls were studied. IR ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 28 publications
1
20
0
1
Order By: Relevance
“…In a very recent study performed by Cadeddu, et al, contractile reserve was shown to be impaired in patients with IR. 35) They performed dobutamine stress echocardiography, and showed impaired strain rate increase in IR patients when compared to the controls. 35) This is the most similar study to ours and their results are compatible with our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a very recent study performed by Cadeddu, et al, contractile reserve was shown to be impaired in patients with IR. 35) They performed dobutamine stress echocardiography, and showed impaired strain rate increase in IR patients when compared to the controls. 35) This is the most similar study to ours and their results are compatible with our study.…”
Section: Discussionmentioning
confidence: 99%
“…35) They performed dobutamine stress echocardiography, and showed impaired strain rate increase in IR patients when compared to the controls. 35) This is the most similar study to ours and their results are compatible with our study. However, their patient size was smaller than our study (30 IR patients and 20 controls) and some of their patients had controlled HT.…”
Section: Discussionmentioning
confidence: 99%
“…From another point of view, long standing IR may have deleterious effect on LV diastolic function. C. Cadeddu et al demonstrated that even isolated IR may adversely affect cardiac function, as evidenced by reduced global LSR at peak of dobutamine stress test [10]. The manifestation of type 2 DM in HTN is associated with signifi cant decrease of both systolic and diastolic speckle tracking markers (global LS and global LSR E ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been postulated that IR in the post-myocardial period may predispose patients to micro vascular, myocardial injury and larger infract size [13]. Emerging evidence supports direct pro atherogenic effect of IR [14,15], as well as its direct adverse effect on myocardial contractility [16].…”
Section: Number Of Patients; Eventsmentioning
confidence: 99%